PENGARUH PENGGUNAAN SPADA TERHADAP MOTIVASI BELAJAR MAHASISWA PADA PROGRAM STUDI TEKNOLOGI PENDIDIKAN ANGKATAN 2024 DI UNIVERSITAS MUHAMMADIYAH MAKASSAR - jongke, Baso; Dr. Aliem Bahri, S.Pd., M.Pd; Firdaus Rahim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of using SPADA on student learning motivation in the 2024 batch of educational technology study program at Muhammadiyah University of Makassar. This study uses a quantitative approach with an experimental method, namely pre-experimental design (One Shot Case Study). The results of the study show that the use of SPADA on student learning motivation in the Educational Technology Study Program class of 2024 at Muhammadiyah University of Makassar has a very good influence. The results of descriptive and inferential statistical analysis when using SPADA, it is known that the observation results show that the high level of satisfaction with the use of SPADA found during learning activities is 94.53% (Very good). Then in the results of observations on the use of SPADA the level of student satisfaction is 91.79% (Very good). The results of the questionnaire show a positive response to the use of SPADA. It can be seen from the dominance of answers in the "agree" and "strongly agree" categories which reached 199 out of 256 responses with an average number showing a score of 4.00. The results of the Pearson correlation mean value are 12.81250 with a sig (2 tailed) of 0.000. This shows that there is an influence of the use of SPADA on student learning motivation because the significant value is based on the decision, namely if the significant value is smaller than 0.05.